Pembelajaran Orang Dewasa Tranformasi Digital: SLR Review VOSviewer - Farah Yusrina; Nadiyah Zahro Athiroh; Nurlaela Hamidah (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
The digital transformation of learning has fundamentally changed the landscape of adult education, demanding complex psychological adaptations from learners. This study aims to analyze the psychological adaptation patterns of adult learners in facing the shift in learning paradigm from conventional to digital. This study aims to map trends, development patterns, and research gaps in the scientific literature on digital transformation in adult education. The method used is a bibliometric approach combined with systematic literature reflection (SLR), with data sourced from Google Scholar and keyword map analysis conducted using VOSviewer software. The results show that digital transformation is the most dominant theme closely related to the topics of education, development, and empirical studies. This analysis reveals a shift in research focus towards an exploratory approach to andragogy in the context of educational digitalization, although its integration in the literature is still very limited. These findings imply that the integration of andragogy frameworks in digital educational transformation is a significant research area and needs further development